Autophagy Inhibition to Increase Radiosensitization in Breast Cancer - Liang, Diana Hwang (J Nucl Med Radiat Ther, 2015)
Currently, many breast cancer patients with localized breast cancer undergo breast-conserving therapy, consisting of local excision followed by radiation therapy. Following radiation therapy, breast cancer cells are noted to undergo induction of autophagy, development of radioresistance, and enrichment of breast cancer stem cell subpopulations. It is hypothesized that inhibition of the cytoprotective autophagy that arises following radiation therapy increases radiosensitivity and confers longer relapse-free survival by eliminating tumor-initiating breast cancer stem cells. Therefore, we reviewed the controversial role of autophagy in breast cancer tumorigenesis and progression, autophagy induction by radiotherapy, and utilization of autophagy inhibitors to increase radiosensitivity of breast cancer and to target radioresistant breast cancer stem cells.